Production and quality evaluation of a novel γ-aminobutyric acid-enriched yogurt - Zhu, Fei; Hu, Sheng; Mei, Lehe (Frontiers in Nutrition, 2024)
Objective γ-aminobutyric acid (GABA) is a neurotransmitter inhibitor that has beneficial effects on various health conditions such as hypertension, cognitive dysfunction, and anxiety. In this study, we investigated a novel yogurt naturally enriched with GABA using a Levilactobacillus brevis strain isolated in our laboratory; the specific optimum yogurt production conditions for this strain were determined. Methods We isolated an L. brevis strain and used it to produce yogurt naturally enriched with GABA. We explored the optimal conditions to enhance GABA yield, including fermentation temperature, inoculation amount, L-monosodium glutamate (L-MSG) concentration, fermentation time, and sucrose content. We also performed mixed fermentation with Streptococcus thermophilus and evaluated the quality of the yogurt. Results Following optimization (43°C, 8% inoculation amount, 1.5 g/L L-MSG, and 8% sucrose for 40 h of fermentation), the GABA yield of the yogurt increased by 2.2 times, reaching 75.3 mg/100 g. Mixed fermentation with S. thermophilus demonstrated favorable results, achieving a GABA yield akin to that found in some commercially available functional foods. Moreover, the viable microbe count in the GABA-enriched yogurt exceeded 1 × 108 cfu/mL, which is higher than that of commercial standards. The yogurt also exhibited a suitable water-holding capacity, viscosity, 3-week storage time, and favorable sensory test results. Conclusion This study highlights the potential of naturally enriched GABA yogurt as a competitive commercial yogurt with beneficial health effects.